2016
DOI: 10.1002/14651858.cd007572.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Anti-IL-12/23p40 antibodies for induction of remission in Crohn's disease

Abstract: High quality evidence suggests that ustekinumab is effective for induction of clinical remission and clinical improvement in patients with moderate to severe Crohn's disease. Moderate to high quality evidence suggests that the optimal dosage of ustekinumab is 6 mg/kg. Briakinumab and ustekinumab appear to be safe. Moderate quality evidence suggests no increased risk of serious adverse events. Future studies are required to determine the long-term efficacy and safety of ustekinumab in patients with moderate to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 57 publications
0
43
0
4
Order By: Relevance
“…It was approved for the treatment of patients with moderate-to-severe CD who have failed or were intolerant to treatment with corticosteroids, immunosuppressives, or anti-TNF therapy. Ustekinumab has shown to be effective in inducing and maintaining remission [29,30], with higher response rates in TNF-naïve than in TNF-experienced patients (54-58% vs. 34%, respectively) [31]. In the updated ECCO guideline [13], ustekinumab has an expanded position within the approved biologicals as it can also be used as a first-line biological -such as vedolizumab.…”
Section: Medical Therapy For CDmentioning
confidence: 99%
“…It was approved for the treatment of patients with moderate-to-severe CD who have failed or were intolerant to treatment with corticosteroids, immunosuppressives, or anti-TNF therapy. Ustekinumab has shown to be effective in inducing and maintaining remission [29,30], with higher response rates in TNF-naïve than in TNF-experienced patients (54-58% vs. 34%, respectively) [31]. In the updated ECCO guideline [13], ustekinumab has an expanded position within the approved biologicals as it can also be used as a first-line biological -such as vedolizumab.…”
Section: Medical Therapy For CDmentioning
confidence: 99%
“…19 Although no reviews reported using a citation index for backward citation searching, only three reviews (2%) explicitly stated that a manual approach was used. 38,48,59 Reports of citation searching in some reviews used phrases suggestive of manual checking rather than a citation index, such as "we scanned the reference lists of relevant studies," but we felt this was still not fully transparent. Hence, these are recorded as manual (assumed) in Table 4.…”
Section: Reporting Of Citation Searchingmentioning
confidence: 99%
“…[164][165][166] In an SR&MA of these 4 trials (n ¼ 1947), ustekinumab was significantly better than placebo for the outcome of failure to achieve remission (RR, 0.91; 95% CI, 0.86-0.95). 167 Two RCTs were conducted in patients who had previously failed anti-TNF therapy. 164,165 In CERTIFI, there were no significant differences in remission rates at week 6, despite ustekinumab being associated with a higher response rate compared to placebo.…”
Section: Non-anti-tumor Necrosis Factor Biologic Therapymentioning
confidence: 99%
“…164 In the SR&MA, there were no significant differences in the rates of adverse events, serious adverse events, or withdrawals due to adverse events. 167 No RCTs assessing ustekinumab in pediatric patients with CD were found.…”
Section: Non-anti-tumor Necrosis Factor Biologic Therapymentioning
confidence: 99%